Refleksi Fenomena Judicialization of Politics pada Politik Hukum Pembentukan Mahkamah Konstitusi dan Putusan Mahkamah Konstitusi - Perwira, Indra (Mahkamah Konstitusi Republik Indonesia, 2016)
This paper aimsÂ toÂ introduceÂ theÂ phenomenonÂ ofÂ judicializationÂ ofÂ politics in the treasury ofÂ legalÂ thoughtÂ inÂ Indonesia.Â InÂ addition,Â thisÂ paperÂ alsoÂ aims to reflect the presence of judicialization of politics in theÂ ConstitutionalÂ Court, either through legal policyÂ onÂ establishmentÂ ofÂ constitutionalÂ courtÂ orÂ through its decisions. Theoretically, the phenomenon of judicialization of politics began to be known at the beginning of the 21st century characterized by the dependence of society to the court to resolve the issues related to morality, public policy, and political controversies. The presence of judicialization of politics can be reflected from the shift in the political settlement of the case which was originally made through political mechanisms to the settlement through a judicial mechanism. To see the phenomenon, this paper will explore the legal policy on establishment of the Constitutional Court. Through a historical perspective on the establishment, this paper would like to indicate that, in nature, the Constitutional Court is a political institution. In addition, this paper also analyzes the Constitutional Court decision in the case of judicial review on â€œPerpuâ€ of the Corruption Eradication Commission (KPK) and the decision regarding the dispute Election East Java province in 2008,Â to show that the phenomenon of judicialization of politics has lived and practicedÂ in the Constitutional Court as well.